Perancangan Aplikasi Permainan Let’s Say dengan Interaksi Pengenalan Ucapan - Andhika Dewanta; R. Rizal Isnanto; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
Computer games has been widespread. Currently, almost all devices that have a screen can play the game with the experience of interactivity to entertain the public. The game does not always have a negative effect. Game application that has a learning function will be useful and easily accepted by society. This study was conducted to determine how computer games can be a fun medium of information and learning by making use of speech recognition interaction. The application development of this